1554. Epidemiology of Adult Bacterial Hand Infections at Two Urban Hospitals. (31st December 2020) - Yassin, Arsheena; Stavropoulos, Christine; Woods, Krystina L; Xu, Jiashan; Carale, Justin; Khachaturyan, Elena; Taduran, Chris; Sy, Hendrik; Farkas, Andras
Abstract: Background: Hand infections represent a major source of morbidity, which can result in hand stiffness and amputation. Early appropriate empiric antibiotic regimen may reduce the associated morbidity, hence the importance to examine local epidemiology. The aim of this study was to define the current epidemiology of adult hand infections at two urban hospitals in New York City. Methods: We performed a double center, retrospective study of adult patients hospitalized from March 2018 to May 2020. Patients with positive cultures associated with the hand infections were included. Retrospectively, 100 patients were reviewed. Data on baseline demographic, clinical, surgical, microbiology, and treatment parameters were collected. Results: Of the 100 patients, 76% were male, with median age of 47.5 years (35, 58.25) and average C-reactive protein (CRP) of 50.66 mg/L (± 64.64) on admission (see Table 1). Previous hospitalization within 1 year (38%), previous surgical procedures (39%) and recent IV medication use (26%) were common. 130 bacterial isolates were identified (see Table 2). The most frequent organisms were Gram-positive, with Methicillin susceptible Staphylococcus aureus (MSSA, 25.38%), Streptococcus species (20.08%), and Methicillin resistant Staphylococcus aureus (MRSA, 15.38%) being the most common. Gram-negative organisms were infrequent, with Haemophilus parainfluenzae (3.85%), Enterobacter cloacae (3.85) and Pseudomonas aeruginosa (3.08%) being the most prevalent. Of the 100 patients, 27% had polymicrobial infections, associated with trauma (6%), illicit IV use (6%) and unknown (7%) etiologies. Table 1: Baseline demographics and co-morbid conditions Table 2: Types and numbers of organisms in relation to etiologies Conclusion: Within our population, the most common organisms associated with hand infections were Gram-positive, with Staphylococcus aureus and Streptococcus species being the most prevalent. Gram-negative pathogens were infrequently isolated. The results within this study can provide guidance to clinicians on assessing the appropriate empiric antibiotic regimen in patients with hand infections, and can serve as a basis for further studies identifying risk factors associated with isolation of organisms associated with hand infections. Disclosures: All Authors : No reported disclosures